The Role of Sleep in the Transition from Acute to Chronic Musculoskeletal Pain in Youth-A Narrative Review - Alessandro Andreucci; Cornelius B. Groenewald; Michael Skovdal Rathleff; Tonya M. Palermo (MDPI AG, 2021)
Musculoskeletal pain is common in the general pediatric population and is a challenge to youth, their parents, and society. The majority of children experiencing musculoskeletal pain will recover; however, a small subgroup of youth develops chronic pain. There is limited understanding of the factors that affect the transition from acute to chronic pain in youth. This review introduces sleep deficiency in the acute to chronic pain transition, exploring the potential mediational or mechanistic role and pathways of sleep in this process, including the interaction with sensory, psychological, and social components of pain and highlighting new avenues for treatment. Biological mechanisms include the increased production of inflammatory mediators and the effect on the hypothalamus-pituitary-adrenal (HPA) axis and on the dopaminergic signaling. Psychological and social components include the effect of sleep on the emotional-affective and behavioral components of pain, the negative impact on daily and social activities and coping strategies and on the reward system, increased pain catastrophizing, fear of pain, pain-related anxiety, hypervigilance, and social isolation. Future longitudinal studies are needed to elucidate these mechanistic pathways of the effect of sleep on the transition from acute to chronic pain, which may lead to the development of new treatment targets to prevent this transition.